2019
DOI: 10.3846/mbmst.2019.006
|View full text |Cite
|
Sign up to set email alerts
|

Change of soil mechanical properties due to triaxial sample size

Abstract: Triaxial test is widely used to determine the behaviour and strength parameters of soil. Several consolidated drained triaxial compression tests were performed on two specimen sizes of sand and clay. This article investigate and compares the influence of specimen size and scale effect on the soil shear strength. The tests results show that the shear strength parameters are influenced by the clay specimen size. The results indicate that the effect of triaxial clay sample size is more significant with higher con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Despite the difficulty in transporting and drilling, large-sized soil sample specimens might represent the actual soil specimens in the field. This difference in the UCS value of the cohesive soil from the smallest specimen diameter to the largest specimen diameter was relatively smaller than that mentioned in [14,20]. Both studies were conducted on specimen size effects using the triaxial test.…”
Section: Effect Of H/d Ratio On Ucsmentioning
confidence: 77%
“…Despite the difficulty in transporting and drilling, large-sized soil sample specimens might represent the actual soil specimens in the field. This difference in the UCS value of the cohesive soil from the smallest specimen diameter to the largest specimen diameter was relatively smaller than that mentioned in [14,20]. Both studies were conducted on specimen size effects using the triaxial test.…”
Section: Effect Of H/d Ratio On Ucsmentioning
confidence: 77%
“…(1) Many scholars [27][28][29] have studied the size effect of soil and found that when the aspect ratio of the samples is 2 : 1 and the minimum size is 10 times larger than the maximum particle size, the final test results are less affected by the size of samples (2) Limitations in the size of the test apparatus used in this paper: the apparatus used was designed to be used for in situ CT scanning during permafrost loading to facilitate comparison with the fine view structures obtained from subsequent CT scans After the specimen is saturated, the isotropic consolidation is performed on the specimen, the pressure was stabilized until the axial strain rate was less than 0.01 mm/h, the specimen was frozen under pressure for 70 min to make the internal temperature of the specimen uniform. After freezing was completed, it was loaded according to different strain rates and stopped loading at 20% strain rate limit.…”
Section: Methodsmentioning
confidence: 99%
“…Wang [21] conducted a triaxial shear test for consolidation and drainage under different conditions, and explored the effects of grain size and confining pressure on the shear characteristics of coral sand in terms of critical confining pressure and shear strength, respectively, and found that the effect of grain size on strength mainly depends on the change of pore ratio. Skuodis [22] found that when the particle size of sand is small, its strength parameters are basically not affected by the sample size, and therefore it is feasible to use a small-sized frozen sand sample.…”
Section: Introductionmentioning
confidence: 99%